A meaningful reminder on sustainability: When explicit and implicit packaging cues meet. (February 2022) - Granato, Giulia; Fischer, Arnout R.H.; van Trijp, Hans C.M.
Abstract: Sustainable packaging innovations are becoming increasingly available in the marketplace. However, their communication to consumers remains a challenging task, as neither their distinctiveness nor their higher sustainability level is recognized. Contributing to research in environmental psychology, the current work conceptualized and tested the new concept of Meaningful Reminder as a strategy to communicate such distinctiveness and higher sustainability. To understand how a meaningful reminder can be created and used, this research investigated how eco explicit (logos, labels and statements) and implicit packaging design cues (auditory, tactile and visual elements) combine and interact and how such a combination can be used to the advantage of sustainability, to increase sustainability salience, perception and sustainable disposal behavior of the packaging and its content. Across three lab studies and different measures (lexical decision task, thought listing task, self-reported scales and observations of consumers' disposal behavior), we identify the conditions under which combining explicit and implicit cues can be counterproductive, not leading to any increase or even a decrease in sustainability salience and perception. However, under different conditions, we show how sustainability salience, perception of packaging sustainability and even consumer sustainable disposal behaviour can be positively affected. Highlights: Explicit cues with meaningless implicit cues increase salience and perception. Explicit cues do not add any effect to an already meaningful implicit cue. The effect of explicit and implicit cues extends to sustainable disposal behaviour. Sensory properties of eco materials can communicate sustainability. A meaningful reminder signals distinctiveness and sustainability.